Is it possible to develop some elements of metacognition in a Mathematics classroom environment? - Kiss, Márton; Kónya, Eszter (Teaching Mathematics and Computer Science, 2020)
In an earlier exploratory survey, we investigated the metacognitive activities of 9th grade students, and found that they have only limited experience in the “looking back” phase of the problem solving process. This paper presents the results of a teaching experiment focusing on ninth-grade students’ metacognitive activities in the process of solving several open-ended geometry problems. We conclude that promoting students’ metacognitive abilities makes their problem solving process more effective.Subject Classification: 97D50, 97G40